Species-specific landscape characterisation method in agro-ecosystems - Łukasz Mikołajczyk (Elsevier, 2021)
The landscape structure of an agro-ecosystem can directly influence its biodiversity. In order to better understand the ongoing worldwide biodiversity collapse, a comprehensive landscape characterisation method is indispensable. In this paper we propose a robust and universal methodological approach to describe agricultural landscape properties tailored for the species of interest. In the proposed method we advocate for using species-specific classes of landscape elements and proper spatial scale reflecting the species home range. As a result, complex landscape description is reduced to relatively few main landscape shaping factors that can serve as landscape metavariables in any further analysis of choice. As a working example, we used a non-metric multidimensional scaling-based method to evaluate how the landscape-level spatial properties of two distinct agricultural landscapes – dominated either by large-scale industrial agriculture or by traditional small-scale farming – shape the environment available to the red mason bee (Osmia bicornis) at different spatial scales. The results for the landscapes studied herein suggest that for pollinators with a home range radius above ca. 100 m, not only local habitat counts but also large-scale landscape properties are of prime importance. This means that for a successful management of biodiversity of such species, large-scale landscape structure must be considered.